Functional influence of botulinum neurotoxin type A treatment (Xeomin®) of multifocal upper and lower limb spasticity on chronic hemiparetic gait - Maurizio Falso; Rosalba Galluso; Andrea Malvicini (MDPI AG, 2012)
This report describes the modification of hemiplegic shoulder pain and walking velocity through injections of Xeomin®, a new botulinum neurotoxin type A formulation, in a 67-year-old woman with chronic residual left hemiparesis and hemiparetic gait attributable to stroke. Clinical evaluation included upper and lower limb spasticity, upper and lower limb pain, trunk control, upper and lower limb motricity index, visual gait analysis, and gait velocity. Assessments were performed before, 1 week after, and 1 month after treatment. Improvement was observed in all clinical parameters assessed. Amelioration of spasticity of the upper and lower limbs and shoulder pain was observed after 1 month. Trunk postural attitude and paraxial muscle recruitment recovered. No adverse events were observed and the patient shows significant improvement of functional impairment derived from chronic spasticity after treatment with Xeomin®. We also provide a simple and useful protocol for clinical evaluation of the treatment.